1998
DOI: 10.1002/(sici)1099-0917(199812)7:4<203::aid-edp182>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of emotion after acute pain from 3 to 18 months: a longitudinal study

Abstract: The object of this study is the stability of emotional regulation after painful events during early development. Thirty subjects' facial expressions were longitudinally observed at 3, 5, 11 and 18 months for 60 s before and 90 s after a paediatric vaccination. The results confirmed that regulation of pain increases with increasing age. Stability was found between 3 and 5 months, but not between 3 and 11 months, thus suggesting that at 5–6 months, there may be a developmental shift towards better regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
9
1
Order By: Relevance
“…Such an interpretation would suggest that the intensity of pain response may be a more stable temperamental characteristic (Rothbart & Dewberry, 1981). Although our findings concerning the stability of intensity of crying were somewhat mixed, they provide modest support for the previous literature indicating stability in the intensity of infants' and children's pain response (e.g., Axia & Bonichini, 1998;Izard et al, 1987;Schechter et al, 1991;Worobey & Lewis, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Such an interpretation would suggest that the intensity of pain response may be a more stable temperamental characteristic (Rothbart & Dewberry, 1981). Although our findings concerning the stability of intensity of crying were somewhat mixed, they provide modest support for the previous literature indicating stability in the intensity of infants' and children's pain response (e.g., Axia & Bonichini, 1998;Izard et al, 1987;Schechter et al, 1991;Worobey & Lewis, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the infant pain response changes over time (Axia & Bonichini, 1998), and older infants are known to seek out their mothers' faces to gauge how to respond emotionally to an event that is ambiguous (i.e., "social referencing;" Moses, Baldwin, & Rosicky, & Tidball, 2001). As such, the present study provides preliminary evidence that maternal facial expressions are important to examine within the context of infants' pain experiences.…”
Section: Limitationsmentioning
confidence: 69%
“…These data also contribute to a growing literature on the social context of infant crying in Western and other cultural contexts (Axia and Bonichini 1998;Barr et al 1991;Bond et al 2001;Gray et al 2000;K. Lee 2000;McGlaughlin and Grayson 2001).…”
Section: Discussionmentioning
confidence: 99%